Cover Picture. Issue 4 (19th August 2021) - Unknown
Abstract : We demonstrate a moth‐eye‐inspired structure for light‐trapping photons to which the human eye is less perceptive. This biomimetic structure contributes to the improvements in performance and visual appearance of semi‐transparent perovskites solar cells simultaneously. Consequently, a record high figure‐of‐merit, defined as the product of PCE and AVT, is achieved. Meanwhile, the optical appearance is converted to a desired near‐neutral color. Abstract : We demonstrate a moth‐eye‐inspired structure for light‐trapping photons to which the human eye is less perceptive. This biomimetic structure contributes to the improvements in performance and visual appearance of semi‐transparent perovskites solar cells simultaneously. Consequently, a record high figure‐of‐merit, defined as the product of PCE and AVT, is achieved. Meanwhile, the optical appearance is converted to a desired near‐neutral color.